Unregistered Marriages in Sabah: Indonesian Migrant Workers at the Crossroads of Faith, Law, and Livelihood - Wahib, Ahmad Bunyan; Hayat, Muhammad Jihadul; Awang, Nurulbahiah (Journal of Human Rights, Culture and Legal System, 2025)
The immigration policy of Malaysia prohibits migrant workers from marrying during their employment contract, whether with fellow migrant workers or Malaysian citizens. However, despite this prohibition, the practice of marriage between Indonesian migrant workers, often referred to as kawin kampung (village marriage), has been prevalent for many years in Sabah, Malaysia. This marriage practice occurs without the involvement of the state and is not officially registered, thus classified as an unofficial or nikah sirri (secret marriage). Nevertheless, such marriages are recognized socially within the community, even though they are not legally acknowledged (illegal but licit). This research aims to explain the structure and agency involved in marriage practice among Indonesian migrant workers. Taking the floor in Sabah, Malaysia, data were gathered through interviews with related parties in the field. This research employs Giddens' theory of structuration. This research argues that the practice of kawin kampung (village marriage) among Indonesian migrant workers (PMI) in Sabah, is a multifaceted issue influenced by a combination of religious, legal, economic, and social factors. Their religious belief constitutes an essential foundation for sustaining life within the oil palm plantations. Although their marriages cannot be categorized as legally valid under the Malaysian state law, they are many times underhand allowed by the company and can gradually and annually be submitted for official validation (isbat nikah) at the Indonesian representative office. Inconsistent law enforcement against undocumented immigrants has enabled their continued entry, thereby perpetuating the practice of unregistered marriages (kawin kampung) among Indonesian migrants.